Analysis of the Digital Literacy Model of the Muarajambi Compound Temple in Increasing Cultural Tourism Promotion on Social Media - Fatya Kariadna; Johannes; Logi Mulawarman (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the community's digital literacy model and formulate strategies for utilizing social media to enhance cultural tourism promotion in the Muarajambi Temple area. The study used a descriptive qualitative approach, involving community members who manage cultural tourism activities as informants. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing and verifying conclusions. The results show that the community's digital literacy has developed in the aspects of information retrieval, hypertextual navigation, content evaluation, and knowledge management. However, these competencies are still self-taught, resulting in social media management that has not been carried out in a planned, consistent, and sustainable manner. This condition causes digital promotion to focus more on disseminating basic information, thus failing to encourage tourists to make a decision to visit. Analysis using the AIDDA model shows that the promotional strategy implemented is still dominant at the awareness and interest stages, while the desire, decision, and action stages have not been optimized. Therefore, strengthening human resource capacity, developing a systematic content strategy, and sustainable social media management are needed to make cultural tourism promotion in the Muarajambi Temple area more effective in increasing destination attractiveness and increasing tourist visits